Diagnostic Accuracy of Extended Focused Assessment with Sonography For Trauma (E-FAST) Keeping Contrast Enhanced CT Chest And Abdomen As Gold Standard - Gul, Bibi; Anwar, Javed; Pervaiz, Hafiz Khalid; Niaz, Ayesha; Sultana, Nasira; Tariq, Mehwish (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of extended focused assessment with sonography for trauma (E-FAST) for detecting thoraco-abdominal trauma, keeping contrast-enhanced CT chest and abdomen as the gold standard. Study Design: Cross-sectional study. Place and Duration of Study: Department of Radiology, Combined Military Hospital, Quetta, from Jan 2020 to Aug 2021. Methodology: A total of (n=196) patients, of age 18-60 years, of both genders, who sustained thoraco-abdominal injuries and were referred for contrast-enhanced Computed tomography of the chest and abdomen were enrolled in the study. Patients were subjected to the thorax and abdomen ultrasonographic examination first and then underwent a contrast-enhanced CT scan of the thorax and abdomen. The findings of both modalities were recorded and subjected to statistical analysis to confirm the accuracy of ultrasound, considering CT-scan as a gold standard procedure. Results: The mean age of the patients was 35 10.6. There were 164 (83.7%) males and 32 (16.3%) females. Blunt trauma was seen in 131 (66.8%) and penetrating trauma in 65 (32.2%) patients. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of E-FAST for chest trauma was 79.4%, 94.7%, 87.6%, 90.7% and 89.8% respectively, for abdominal trauma was 68.6%, 95.2%, 88.8%, 84.5% and 85.7% respectively and for combined chest and abdominal trauma was 77.1%, 95.9%, 85.9%, 92.8% and 91.3% respectively. Conclusion: E-FAST has good diagnostic accuracy for the chest, abdominal and both thoraco-abdominal trauma and can be incorporated into the routine assessment of patients presenting with trauma.